2016
DOI: 10.21276/aimdr.2016.2.4.49
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Distribution Width (PDW) - A Rarely Studied Platelet Indice for Determining the Causes of Thrombocytopenia

Abstract: Background: Thrombocytopenia (TCP) is low platelets count, which is either due to defective platelet production or due to increased platelet breakdown. The platelet number alone does not give a complete picture of platelet maturity and function, therefore, the platelet indices have been the subject of intensive study in recent years, but they have not been firmly established. Mean platelet volume (MPV) and platelet distribution width (PDW) are useful parameters in evaluating disorders of platelets. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Males were predominantly affected in hypo productive and hyper destructive thrombocytopenia with 41.4% and 58.6%. Dengue (19) and malaria (11) Pearson correlation between the platelet count and platelet indices in hyper destructive TCP cases shows positive correlation for MPV 0.067 with a p value of 0.64 which is statistically not significant. There is a negative correlation between the platelet count and platelet indices PDW -0.001 and PLCR -0.113 with a p value of 0.99 and 0.44 which is statistically not significant (Fig.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Males were predominantly affected in hypo productive and hyper destructive thrombocytopenia with 41.4% and 58.6%. Dengue (19) and malaria (11) Pearson correlation between the platelet count and platelet indices in hyper destructive TCP cases shows positive correlation for MPV 0.067 with a p value of 0.64 which is statistically not significant. There is a negative correlation between the platelet count and platelet indices PDW -0.001 and PLCR -0.113 with a p value of 0.99 and 0.44 which is statistically not significant (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…5 Studies done by kharikar et al mentioned that Babu E and Basu D suggested that it is not always possible to record platelet indices in the presence of red cell fragmentation, in severe thrombocytopenia. 11 We also avoided this problem by discarding cases without indices and selected only those cases which had platelet indices and provided a histogram. In the present study we are used Sysmex XN1000 hematology fully automated analyzer which works on the principal of hydrodynamic focusing and flow cytometry.…”
Section: Roc Curve Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…[2,9,10] The analyzers also display a plateletogram along with numerical indices which are often overlooked. [4] Other than the routine platelet counts, which is the most commonly asked parameter, the other platelet indices like MPV [Mean platelet volume], PCT [plateletcrit] and PDW [platelet distribution width] are also available in the analyzer readings. [10,11] Majority of the thrombocytopenic cases in our study fell into the third decade of life, with the male to female ratio being 1.3:1, similar to the study done by Borkataky et al [12] This dominant age group could be attributed to the large load of viral infections in our area affecting young population working outdoors.…”
Section: Discussionmentioning
confidence: 99%
“…These analyzers routinely give platelet histogram in addition to platelet count and indices at no extra cost. [3,4,5] However, the histogram is often neglected, with the main emphasis being only on the platelet counts. [6] A good basic knowledge on the interpretation of histograms can be a useful adjunct tool along with platelet indices to determine the underlying mechanism of thrombocytopaenia.…”
Section: Introductionmentioning
confidence: 99%